Ti Emoi Kai Σoi - Maynard, Arthur H. (New Testament studies, 1985)
In John 2. 4 there is a peculiar Greek idiom which has not only given almost every translator difficulty, but which is, in the opinion of the writer, both a key to the way in which the author of the Fourth Gospel used his sources, and to his interpretation of Jesus. The verse reads ‘And Jesus said to her: τί έμοί καί σοί; woman, my hour has not yet come.’